Levofloxacin prophylaxis for pediatric leukemia patients: monitoring of outcomes for sustained benefit and consequences - Andrea L. Davis; Alexandra M. Stevens; Julienne Brackett; Lucila Marquez; Catherine E. Foster; Adriana Sarmiento Clemente; Hannah E. Sauer; Grant T. Stimes; Judith R. Campbell (Cambridge University Press, 2024)
Levofloxacin prophylaxis reduces bloodstream infections in neutropenic patients with acute myeloid leukemia or relapsed acute lymphoblastic leukemia. A retrospective, longitudinal cohort study compares incidence of bacteremia, multidrug-resistant organisms (MDRO), and Clostridioides difficile (CDI) between time periods of levofloxacin prophylaxis implementation. Benefits were sustained without increasing MDRO or CDI.